Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1039/c8ta11296g
|View full text |Cite
|
Sign up to set email alerts
|

Electroforming of a metal–organic framework on porous copper hollow fibers

Abstract: Porous hollow fibers are used for the first time as both support and metal source for electroforming of MOF films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…In recent years, a considerable number of researchers have been committed to improving ADS for developing new MOF crystals by the replacement of substrate, [44][45] the employment of additional templates [46][47] and adding structure-directing agents. [48] Moreover, ADS has greatly helped to innovate the synthesis of MOFs (as well as their complexes) and broaden their practical applications.…”
Section: Anode Dissolution Synthesismentioning
confidence: 99%
“…In recent years, a considerable number of researchers have been committed to improving ADS for developing new MOF crystals by the replacement of substrate, [44][45] the employment of additional templates [46][47] and adding structure-directing agents. [48] Moreover, ADS has greatly helped to innovate the synthesis of MOFs (as well as their complexes) and broaden their practical applications.…”
Section: Anode Dissolution Synthesismentioning
confidence: 99%
“…Although studies on MOF films on various copper supports such as plates, disks, meshes, beads and copper coated silicon wafers, using gold and glass carbon electrodes, were reported, electrochemical deposition of MOFs directly on porous hollow fibers (HFs) have not been reported. Demirel et al [72] reported on the thin metal organic framework (Cu-BTC, (Cu 3 (BTC) 2 ,BTC =benzene-1,3,5-tricarboxylate) films on Cu-HFs, to study the effect of the presence of a supporting electrolyte and the magnitude of the applied electrical potential on the formation and the morphology of the films. In the presence of a supporting electrolyte, formation of less homogeneous films and the growth of MOF crystals were observed in the liquid, whereas, in the absence of a supporting electrolyte, and at low potential, more uniform films with smaller particles were obtained.…”
Section: Inorganic Membranesmentioning
confidence: 99%
“…The electrochemical strategy makes use of the anodic oxidation or cathodic reduction reactions to trigger the crystallization of MOF materials. , In the anodic deposition, oxidation of metal electrodes of various types generates the corresponding metal ions, which subsequently react with organic ligands in the electrolytic solution to form MOF materials on the surface of anode. In the cathodic deposition, the reduction of a probase (such as water, triethylammonium, and nitrates) on electrode causes an increase in pH nearby, which deprotonates organic ligands to trigger the formation of MOFs on the cathode surface. Although the cathodic method does not limit electrode materials for MOFs to deposit as compared with the anodic one, it is commonly challenged by the accompanying plating of corresponding metals in the deposition of those MOFs that contain easily reduced metal ions (such as Zn 2+ and Cu 2+ ) due to the large reduction overpotentials of proton and nitrate ions in the probases above-mentioned. , One possible way to address this issue is to use special catalytic electrodes to lower the reduction overpotentials of nitrate ions and proton, for example, zinc for nitrate and platinum for triethylammonium. , Another approach is to seek a more readily reduced probase. In this regard, we demonstrated recently that O 2 can serve as an effective probase to suppress the plating of metallic zinc and cobalt in the electrodeposition of zeolitic imidazolate framework materials (ZIF-8, ZIF-67, and ZIF-71) .…”
Section: Introductionmentioning
confidence: 99%